Original paperIs it worth closing the atrial septal defect in patients with insignificant shunt? - Komar, Monika; Przewłocki, Tadeusz; Olszowska, Maria; Sobień, Bartosz; Tomkiewicz-Pająk, Lidia; Podolec, Piotr (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Introduction: Closure of the atrial septal defect in patients with insignificant shunt is controversial. Aim : To evaluate the outcomes of transcatheter closure of atrial septal defect (ASD) in symptomatic patients with borderline shunt. Material and methods: One hundred and sixty patients (120 female, 40 male) with a mean age of 30.1 ±16.2 (20–52) years with a small ASD who underwent transcatheter closure were analyzed. All patients had a small ASD with Qp : Qs ratio ≤ 1.5, mean 1.2 ±0.9 (1.1–1.5) in echo examination. Cardiopulmonary exercise tests, clinical study, transthoracic echocardiographic study as well as quality of life (QoL) (measured using the SF36 questionnaire (SF36q)) were repeated in all patients before and after the procedure. Results : The devices were successfully implanted in all patients. After 12 months of ASD closure, all the patients showed a significant improvement of exercise capacity (oxygen consumption – 21.9 ±3.1 vs. 30.4 ±7.7, p > 0.001). The QoL improved in 7 parameters at 12-month follow-up. The mean SF36q scale increased significantly in 141 (88.1%) patients of mean 43.2 ±20.1 (7–69). A significant decrease of the right ventricular area (20.3 ±1.3 cm 2 vs. 18.3 ±1.2 cm 2 , p < 0.001) and the right atrial area (15.2 ±1.9 cm 2 vs. 12.0 ±1.6 cm 2 , p < 0.001) was observed at 12-month follow-up. Conclusions: Closure of ASD in the patients with insignificant shunt resulted in significant durable clinical and hemodynamic improvement after percutaneous treatment.